Cobalt-based catalyst for conversion of hydrocarbons to syngas
By using composite oxide catalysts with high lanthanum content, the problem of difficulty in activation of Co-containing catalysts in the prior art is solved, and more efficient catalyst activation and cost-efficiency improvement are achieved.
Patent Information
- Application Number
- CN202380051257.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-01
- Filing Date
- 2023-06-30
- Publication Date
- 2025-02-18
AI Technical Summary
There are difficulties in the activation process of existing Co-containing catalysts, resulting in increased production costs and it is difficult to improve the activation speed and efficiency of the catalyst.
The composite oxide catalyst containing lanthanum is used, with specific components such as oxygen, lanthanum, aluminum and cobalt, and the Co:La weight ratio of cobalt to lanthanum is in the range of 0.06:1 to 0.34:1 to achieve milder activation and improvement Reducibility of catalyst.
By optimizing the composition of the catalyst, the activation speed and efficiency of the catalyst are significantly improved, production costs are reduced, and higher cost efficiency is achieved.
Smart Images

Figure SMS_11 
Figure SMS_12 
Figure SMS_13
Abstract
Description
Technical Field
[0001] The present invention relates to a composite oxide comprising oxygen, lanthanum, aluminum and cobalt, wherein the composite oxide has a specific Co:La weight ratio. In addition, the present invention relates to a method for producing the composite oxide and a composite oxide obtainable or obtained by said method. Still further, the present invention relates to a method for producing a catalyst for converting hydrocarbons into synthesis gas, and a catalyst obtainable or obtained by said method. Still further, the present invention relates to a method for converting hydrocarbons into synthesis gas.
[0002] Detailed description
[0003] Oxide-based catalysts containing Ni or Co are commonly used to reform hydrocarbons into synthesis gas. The use of Co-containing catalysts reduces production costs because they allow lower steam content in the feed. However, difficulties in activating Co-containing catalysts lead to increased production costs because special activation procedures are usually required.
[0004] WO 2013 / 118078 A1 relates to a Ni or Co-containing hexaaluminate catalyst for reforming hydrocarbons. WO2014 / 135642 A1 relates to a Ni-containing hexaaluminate catalyst for reforming hydrocarbons in the presence of CO2. Similarly, WO2015 / 091310 A1 relates to a method for reforming a mixture of hydrocarbons and CO2. US2016 / 0207031 A1 and US9566571 B2 specifically relate to a method for producing a catalyst for reforming hydrocarbons from a feed gas containing methane and CO2.
[0005] On the other hand, WO 2014 / 001423 A1 relates to a high-pressure process for the reforming of hydrocarbons with CO2 in the presence of an Ir-containing catalyst. WO 2015 / 135968 A1, for its part, relates to yttrium-containing catalysts for high-temperature CO2 hydration and / or reforming.
[0006] WO 2016 / 062853 A1 relates to the synthesis of aluminates by flame spray pyrolysis.
[0007] Finally, WO 2020 / 157202 A1 relates to a molding comprising a mixed oxide of lanthanum, aluminum and cobalt, wherein the Co:La weight ratio is specified to be in the range of 0.35:1 to 0.48:1.
[0008] Although many modifications have been made in the past, there remains a need for improved catalyst formulations, particularly with regard to their cost effectiveness, and more particularly with regard to the activation of Co-containing catalysts for the reforming of hydrocarbons to synthesis gas. DETAILED DESCRIPTION
[0009] It is therefore an object of the present invention to provide a Co-containing catalyst formulation, and in particular a Co-containing catalyst formulation for converting hydrocarbons into synthesis gas in the presence of steam and / or CO2, wherein the catalyst formulation allows a gentler activation of the Co-containing catalyst, and in particular wherein the speed of catalyst activation is increased. Thus, it has been unexpectedly found that a Co-containing catalyst formulation containing lanthanum, wherein the Co:La weight ratio is within a specific range, allows a significantly higher reducibility of the catalyst at low temperatures, as a result of which the activation of the catalyst is significantly improved and can therefore be achieved in a much shorter period of time. As a result, it has been quite unexpectedly found that a highly cost-effective Co-containing catalyst can be provided.
[0010] Therefore, the present invention relates to a composite oxide comprising oxygen, lanthanum, aluminum and cobalt, wherein the Co:La weight ratio of cobalt to lanthanum in the composite oxide is in the range of 0.06:1 to 0.34:1, preferably 0.08:1 to 0.32:1, more preferably 0.10:1 to 0.30:1, more preferably 0.12:1 to 0.28:1, more preferably 0.14:1 to 0.26:1, more preferably 0.16:1 to 0.24:1, more preferably 0.18:1 to 0.22:1, and more preferably 0.20:1 to 0.21:1, calculated as the element.
[0011] Preferably, the composite oxide contains 1 to 15 wt.-%, more preferably 3 to 10 wt.-%, more preferably 4 to 8 wt.-%, more preferably 4.5 to 7.5 wt.-%, more preferably 5 to 7.1 wt.-%, more preferably 5.5 to 6.9 wt.-%, more preferably 5.7 to 6.7 wt.-%, more preferably 5.9 to 6.5 wt.-%, and more preferably 6.1 to 6.3 wt.-% cobalt, calculated as the element.
[0012] Preferably, the composite oxide contains 5 to 50 wt.-%, preferably 10 to 45 wt.-%, more preferably 15 to 40 wt.-%, more preferably 20 to 38 wt.-%, more preferably 22 to 35 wt.-%, more preferably 24 to 32 wt.-%, more preferably 26 to 31 wt.-%, and more preferably 28 to 30 wt.-% lanthanum, calculated as the element.
[0013] Preferably, the composite oxide contains 5 to 60 wt.-%, more preferably 10 to 50 wt.-%, more preferably 15 to 45 wt.-%, more preferably 20 to 40 wt.-%, more preferably 23 to 38 wt.-%, more preferably 25 to 35 wt.-%, more preferably 27 to 33 wt.-%, and more preferably 29 to 31 wt.-% aluminum, calculated as the element.
[0014] Preferably, in the composite oxide, the Co:Al weight ratio of cobalt to aluminum is in the range of 0.05:1 to 0.50:1, more preferably 0.10:1 to 0.40:1, more preferably 0.12:1 to 0.30:1, more preferably 0.15:1 to 0.28:1, more preferably 0.18:1 to 0.25:1, and more preferably 0.20:1 to 0.22:1, more preferably in the range of 0.205:1 to 0.22:1, calculated in terms of elements.
[0015] Preferably, the composite oxide contains LaAl 1-x Co x O3 phase, more preferably LaAl 1-x Co x O3 perovskite phase, where 0 < x < 1, and where x is preferably in the range of 0.02 to 0.4, more preferably in the range of 0.03 to 0.3. In this regard, it is particularly preferred that the lattice parameter a of the LaAl 1-x Co x O3 phase is in the range of 3.7920 to more preferably 3.7925 to more preferably 3.7928 to more preferably 3.7930 to and more preferably 3.7932 to the range of,
[0016] wherein in the composite oxide, the lattice parameter a of the LaAl 1-x Co x O3 phase is preferably determined according to the method of Reference Example 1. In addition and independently of this, it is particularly preferred that the composite oxide contains the LaAl 1-x Co x O3 phase, the amount of which ranges from 5 to 50 wt.-% based on 100 wt.-% of the composite oxide, more preferably 10 to 40 wt.-%, more preferably 13 to 35 wt.-%, more preferably 15 to 33 wt.-%, more preferably 18 to 30 wt.-%, more preferably 21 to 27 wt.-%, and more preferably 23 to 25 wt.-%, wherein the amount of the LaAl 1-x Co x O3 phase in the composite oxide is preferably determined according to the method of Reference Example 1.
[0017] Preferably, the composite oxide contains LaCoAl 11 O 19 phase, preferably LaCoAl 11 O 19 hexaaluminate phase.
[0018] In the case where the composite oxide contains LaCoAl 11 O 19In the case of a phase, it is preferred that the composite oxide contains the LaCoAl 11 O 19 phase, the amount of which ranges from 40 to 90 wt.-%, preferably from 50 to 80 wt.-%, more preferably from 55 to 75 wt.-%, more preferably from 58 to 70 wt.-%, more preferably from 60 to 66 wt.-%, and more preferably from 62 to 64 wt.-%, based on 100 wt.-% of the composite oxide, wherein in the composite oxide the LaCoAl 11 O 19 The amount of the phase is preferably determined according to the method of Reference Example 1.
[0019] Preferably, the composite oxide comprises LaAl 1-x Co x O3 phase and LaCoAl 11 O 19 phase, in which the LaAl 1-x Co x O3 phase and LaCoAl 11 O 19 LaAl 1-x Co x O3:LaCoAl 11 O 19 The weight ratio is in the range of 0.05:1 to 0.70:1, preferably 0.1:1 to 0.60:1, more preferably 0.15:1 to 0.55:1, more preferably 0.20:1 to 0.50:1, more preferably 0.25:1 to 0.48:1, more preferably 0.30:1 to 0.45:1, more preferably 0.35:1 to 0.42:1, and more preferably 0.37:1 to 0.39:1, wherein in the composite oxide the LaAl 1-x Co x O3 phase and the LaCoAl 11 O 19 The respective amounts of the phases are preferably determined according to the method of Reference Example 1.
[0020] Preferably, the composite oxide contains a La(OH)3 phase.
[0021] In the case where the composite oxide contains a La(OH)3 phase, it is preferred that the composite oxide contains the La(OH)3 phase in an amount ranging from 0.1 to 1.5 wt.-%, more preferably from 0.3 to 1.0 wt.-%, more preferably from 0.5 to 0.8 wt.-%, and more preferably from 0.6 to 0.7 wt.-%, based on 100 wt.-% of the composite oxide.
[0022] The amount of the La(OH)3 phase in the composite oxide is preferably determined according to the method of Reference Example 1.
[0023] Preferably, the composite oxide comprises a CoAl2O4 phase, more preferably a CoAl2O4 spinel phase.
[0024] In the case where the composite oxide comprises a CoAl2O4 phase, it is preferred that the composite oxide comprises the CoAl2O4 phase in an amount ranging from 1.0 to 10 wt.-%, more preferably from 1.5 to 7.0 wt.-%, more preferably from 2.0 to 5.0 wt.-%, more preferably from 2.5 to 4.0 wt.-%, more preferably from 2.8 to 3.5 wt.-%, and more preferably from 3.0 to 3.2 wt.-%, based on 100 wt.-% of the composite oxide.
[0025] The amount of the CoAl2O4 phase in the composite oxide is preferably determined according to the method of Reference Example 1.
[0026] Preferably, the composite oxide comprises LaAl 1-x Co x O3 phase and CoAl2O4 phase, in which the LaAl 1-x Co x O3 phase and the CoAl2O4 phase 1-x Co x The O3:CoAl2O4 phase weight ratio is in the range of 1.0:1 to 15:1, more preferably 2.0:1 to 12:1, more preferably 4.0:1 to 10:1, more preferably 6.0:1 to 9.0:1, more preferably 7.0:1 to 8.5:1, more preferably 7.5:1 to 8.2:1, and more preferably 7.8:1 to 7.9:1, wherein the LaAl2O4 phase weight ratio in the composite oxide is in the range of 1.0:1 to 15:1, more preferably 2.0:1 to 12:1, more preferably 4.0:1 to 10:1, more preferably 6.0:1 to 9.0:1, more preferably 7.0:1 to 8.5:1, more preferably 7.5:1 to 8.2:1, and more preferably 7.8:1 to 7.9:1. 1-x Co x The respective amounts of the O3 phase and the CoAl2O4 phase are preferably determined according to the method of Reference Example 1.
[0027] Preferably, the composite oxide comprises LaCoAl 11 O 19 phase and CoAl2O4 phase, in which the LaCoAl 11 O 19 The LaCoAl2O4 phase 11 O 19 The weight ratio of LaCoAl2O4 phase is in the range of 1:1 to 50:1, more preferably 3:1 to 45:1, more preferably 5:1 to 40:1, more preferably 9:1 to 35:1, more preferably 11:1 to 30:1, more preferably 13:1 to 28:1, more preferably 15:1 to 26:1, more preferably 18:1 to 24:1, and more preferably 20:1 to 22:1, wherein the LaCoAl2O4 phase weight ratio in the composite oxide is in the range of 1:1 to 50:1, more preferably 3:1 to 45:1, more preferably 5:1 to 40:1, more preferably 9:1 to 35:1, more preferably 11:1 to 30:1, more preferably 13:1 to 28:1, more preferably 15:1 to 26:1, more preferably 18: 11 O 19The phase and the respective amounts of the CoAl2O4 phase are preferably determined according to the method of Reference Example 1.
[0028] Preferably, the composite oxide exhibits a crystallinity ranging from 80% to 100%, more preferably from 85% to 99%, more preferably from 88% to 97%, more preferably from 90% to 95%, and more preferably from 91% to 93%, wherein the crystallinity of the composite oxide is preferably determined according to the method of Reference Example 1.
[0029] Preferably, 99 to 100 wt-%, more preferably 99.5 to 100 wt-%, more preferably 99.9 to 100 wt-% of the composite oxide consists of oxygen, lanthanum, aluminum, cobalt and optionally hydrogen.
[0030] The composite oxide is preferably in the form of a powder or a molded article, more preferably in the form of a molded article.
[0031] In the case where the complex oxide is in the form of a powder or a molding, preferably 99 to 100 wt-%, more preferably 99.5 to 100 wt-%, more preferably 99.9 to 100 wt-% of the powder or the molding consists of the complex oxide.
[0032] Preferably, the composite oxide is obtained or obtainable according to the method of any one of the specific and preferred embodiments of the present invention.
[0033] The present invention also relates to a method for producing a composite oxide, preferably a composite oxide according to any one of the specific and preferred embodiments of the present invention, comprising
[0034] (i) preparing a mixture of one or more Al sources, one or more Co sources and one or more La sources;
[0035] (ii) adding an acidic aqueous solution to the mixture prepared in (i);
[0036] (iii) homogenizing the mixture obtained in (ii),
[0037] (iv) optionally shaping the mixture obtained in (iii), preferably by extrusion, to obtain a shaped body;
[0038] (v) optionally drying the mixture obtained in (iii) or the shaped body obtained in (iv);
[0039] (vi) optionally pre-calcining the mixture obtained in (iii) or (v), or the shaped body obtained in (iv) or (v);
[0040] (vii) optionally grinding the dried and / or precalcined mixture or shaped body obtained in (v) or (vi);
[0041] (viii) optionally tableting the ground product obtained in (vii);
[0042] (ix) calcining the mixture obtained in (iii), (v), or (vi), or the shaped body obtained in (iv), (v), or (vi), or the ground product obtained in (vii), or the tableted product obtained in (viii).
[0043] In addition and independently of this, it is preferred that the one or more Al sources are selected from the group consisting of aluminum hydroxide, Al2O3·0.5H2O, Al2O3, AlO(OH) (preferably boehmite), sodium aluminate and a mixture of two or more thereof, preferably selected from the group consisting of gibbsite (α-aluminum hydroxide), bayerite (β-aluminum hydroxide), nordstrandite (γ-aluminum hydroxide), pseudo-amorphous aluminum hydroxide, Al2O3·0.5H2O, Al2O3, AlO(OH) (preferably boehmite), sodium aluminate and a mixture of two or more thereof, wherein the one or more alumina sources are more preferably AlO(OH).
[0044] Preferably, the one or more Co sources are selected from the group consisting of cobalt carbonate, cobalt oxalate, cobalt acetate, cobalt tartrate, cobalt formate, cobalt sulfate, cobalt sulfide, cobalt fluoride, cobalt chloride, cobalt bromide and cobalt iodide, wherein the one or more Co sources are more preferably cobalt carbonate, more preferably cobalt carbonate, wherein the cobalt carbonate more preferably comprises, more preferably is CoCO3·yH2O, wherein 0≤y≤7, preferably 0≤y≤6.
[0045] Preferably, the one or more La sources are selected from the group consisting of lanthanum carbonate, lanthanum oxalate, lanthanum acetate, lanthanum tartrate, lanthanum formate, lanthanum sulfate, lanthanum sulfide, lanthanum fluoride, lanthanum chloride, lanthanum bromide and lanthanum iodide, wherein the one or more La sources are more preferably lanthanum carbonate, wherein the lanthanum carbonate more preferably comprises, more preferably is, La2(CO3)3·xH2O, wherein 0≤x≤10, more preferably 0≤x≤6.
[0046] Preferably, the mixture in (i) is prepared by kneading the one or more Al, Co and La sources.
[0047] Preferably, the acidic aqueous solution added in (ii) comprises one or more of formic acid, acetic acid, propionic acid, nitric acid, nitrous acid, citric acid, tartaric acid and oxalic acid, more preferably one or more of formic acid and nitric acid, wherein the acidic aqueous solution added in (ii) more preferably comprises formic acid.
[0048] Preferably, the homogenization in (iii) is achieved by stirring, preferably kneading, the mixture obtained in (ii).
[0049] Preferably, the drying in (v) is performed at a temperature in the range of 80°C to 150°C, more preferably in the range of 95°C to 120°C, more preferably in the range of 100°C to 110°C.
[0050] Preferably, the drying in (v) is carried out for a duration in the range of 4 to 18 h, more preferably in the range of 6 to 12 h, more preferably in the range of 8 to 10 h.
[0051] Preferably, the pre-calcination in (vi) is carried out at a temperature in the range of 300°C to 600°C, more preferably in the range of 350°C to 500°C, more preferably in the range of 400°C to 450°C.
[0052] Preferably, the pre-calcination in (vi) is carried out for a duration in the range of 1 to 8 h, more preferably in the range of 3 to 5 h, more preferably in the range of 3.5 to 4.5 h.
[0053] Preferably, the calcination in (ix) is carried out at a temperature in the range of 800°C to 1500°C, more preferably in the range of 1000°C to 1400°C, more preferably in the range of 1100°C to 1300°C.
[0054] Preferably, the calcination in (ix) is carried out for a duration in the range of 1 to 8 h, more preferably in the range of 3 to 5 h, more preferably in the range of 3.5 to 4.5 h.
[0055] Besides this, the present invention relates to a composite oxide obtainable or obtained as a result of the process according to any one of the specific and preferred embodiments of the present invention.
[0056] The invention also relates to a method for producing a catalyst for converting hydrocarbons into synthesis gas, the method comprising
[0057] (1) providing a composite oxide according to any one of the specific and preferred embodiments of the present invention, or preparing a composite oxide according to any one of the specific and preferred embodiments of the present invention;
[0058] (2) Reducing the composite oxide prepared in (1) to obtain a catalyst.
[0059] Preferably, the reduction in (2) is carried out in an atmosphere comprising one or more reducing agents, wherein the one or more reducing agents comprise one or more of methane, hydrogen and carbon monoxide, more preferably methane and / or hydrogen, wherein methane is more preferably used as the reducing agent in (2).
[0060] The reduction in (2) is preferably performed at a temperature ranging from 500°C to 1,200°C, more preferably from 600°C to 1,100°C, more preferably from 700°C to 1,050°C, more preferably from 750°C to 1,000°C, more preferably from 800°C to 950°C, and more preferably from 850°C to 900°C.
[0061] Preferably, the reduction in (2) is carried out at a pressure in the range of 5 to 40 absolute bar, more preferably 10 to 35 absolute bar, more preferably 12 to 30 absolute bar, more preferably 14 to 25 absolute bar, more preferably 16 to 22 absolute bar, and more preferably 18 to 20 absolute bar.
[0062] Preferably, the reduction in (2) is carried out for a duration ranging from 0.5 to 24 h, more preferably from 1 to 18 h, more preferably from 3 to 10 h, and more preferably from 5 to 7 h.
[0063] The present invention also relates to a catalyst for converting hydrocarbons into synthesis gas, obtainable or obtained according to the method of any one of the specific and preferred embodiments of the present invention.
[0064] Furthermore, the present invention relates to a method for converting hydrocarbons into synthesis gas, comprising
[0065] (A) providing a composite oxide according to any one of the specific and preferred embodiments of the present invention, or a catalyst for converting hydrocarbons into synthesis gas obtainable or obtained by the method according to any one of the specific and preferred embodiments of the present invention;
[0066] (B) preparing a gas stream comprising one or more hydrocarbons and one or more of CO2 and H2O;
[0067] (C) contacting the gas stream prepared in (B) with the composite oxide provided in (A) at a temperature ranging from 700°C to 1,200°C, preferably 750°C to 1,100°C, more preferably 800°C to 1,050°C, more preferably 850°C to 1,000°C, and more preferably 900°C to 950°C.
[0068] Preferably, the gas stream produced in (B) comprises one or more hydrocarbons, CO2 and H2O.
[0069] Preferably, the one or more hydrocarbons are selected from the group consisting of C1-C10 alkanes, more preferably C1-C8 alkanes, more preferably C1-C6 alkanes, more preferably C1-C4 alkanes, more preferably C1-C3 alkanes, and more preferably C1-C2 alkanes, wherein more preferably the gas stream prepared in (B) comprises one or more of methane, ethane and propane, wherein more preferably the gas stream prepared in (B) comprises methane and / or ethane, preferably methane, wherein more preferably the one or more hydrocarbons contained in the gas stream prepared in (B) consist of methane and / or ethane, preferably methane.
[0070] Preferably the gas stream prepared in (B) comprises 20 to 80 vol.-%, more preferably 25 to 60 vol.-%, more preferably 30 to 50 vol.-%, more preferably 35 to 45 vol.-%, and more preferably 38 to 42 vol.-% of the one or more hydrocarbons.
[0071] Preferably, the gas stream prepared in (B) comprises 20 to 80 vol.-%, more preferably 25 to 60 vol.-%, more preferably 30 to 50 vol.-%, more preferably 35 to 45 vol.-%, and more preferably 38 to 42 vol.-% CO2.
[0072] Preferably, the gas stream prepared in (B) comprises 1 to 30 vol.-%, more preferably 5 to 25 vol.-%, more preferably 10 to 20 vol.-%, more preferably 12 to 18 vol.-%, and more preferably 14 to 16 vol.-% H2O.
[0073] Preferably, the gas stream prepared in (B) further comprises one or more inert gases, wherein these inert gases are more preferably selected from the group consisting of rare gases, nitrogen and mixtures of two or more thereof, wherein more preferably the gas stream further comprises nitrogen and / or argon, preferably nitrogen.
[0074] In the case where the gas stream prepared in (B) further comprises one or more inert gases, it is preferred that the gas stream prepared in (B) comprises 0 to 25 vol.-%, more preferably 0.5 to 15 vol.-%, more preferably 1 to 10 vol.-%, more preferably 3 to 8 vol.-%, and more preferably 4 to 6 vol.% of the one or more inert gases.
[0075] Preferably, the contacting in (C) is carried out at a pressure in the range of 5 to 40 absolute bar, more preferably 10 to 35 absolute bar, more preferably 12 to 30 absolute bar, more preferably 14 to 25 absolute bar, more preferably 16 to 22 absolute bar, and more preferably 18 to 20 absolute bar.
[0076] Preferably, the contacting in (C) is carried out for 500 to 25,000 hours. -1, more preferably 1,000 to 15,000h -1 , more preferably 3,000 to 10,000h -1 , more preferably 4,000 to 8,000h -1 , and more preferably 5,000 to 7,000h -1 The gas hourly space velocity is within the range.
[0077] The present invention is further illustrated by the following group of examples and the combination of examples obtained by the dependencies and back references as shown. In particular, it should be noted that in each case where a series of examples is mentioned, for example in the context of terms such as "complex oxides as described in any one of Examples 1 to 4", each example in this series is intended to be disclosed clearly to the skilled person, that is, the wording of this term should be understood by the skilled person as synonymous with "complex oxides as described in any one of Examples 1, 2, 3 and 4". In addition, it is explicitly pointed out that the following group of examples is not a group of claims that determines the scope of protection, but represents an appropriate structural part of this specification related to the general and preferred aspects of the present invention.
[0078] 1. A composite oxide comprising oxygen, lanthanum, aluminum and cobalt, wherein the Co:La weight ratio of cobalt to lanthanum in the composite oxide is in the range of 0.06:1 to 0.34:1, preferably 0.08:1 to 0.32:1, more preferably 0.10:1 to 0.30:1, more preferably 0.12:1 to 0.28:1, more preferably 0.14:1 to 0.26:1, more preferably 0.16:1 to 0.24:1, more preferably 0.18:1 to 0.22:1, and more preferably 0.20:1 to 0.21:1, calculated as the element.
[0079] 2. A composite oxide as described in Example 1, wherein the composite oxide contains 1 to 15 wt.-%, preferably 3 to 10 wt.-%, more preferably 4 to 8 wt.-%, more preferably 4.5 to 7.5 wt.-%, more preferably 5 to 7.1 wt.-%, more preferably 5.5 to 6.9 wt.-%, more preferably 5.7 to 6.7 wt.-%, more preferably 5.9 to 6.5 wt.-%, and more preferably 6.1 to 6.3 wt.-% cobalt, calculated as the element.
[0080] 3. A composite oxide as described in Example 1 or 2, wherein the composite oxide contains 5 to 50 wt.-%, preferably 10 to 45 wt.-%, more preferably 15 to 40 wt.-%, more preferably 20 to 38 wt.-%, more preferably 22 to 35 wt.-%, more preferably 24 to 32 wt.-%, more preferably 26 to 31 wt.-%, and more preferably 28 to 30 wt.-% lanthanum, calculated as the element.
[0081] 4. The composite oxide according to any one of Examples 1 to 3, wherein the composite oxide contains 5 to 60 wt.-%, preferably 10 to 50 wt.-%, more preferably 15 to 45 wt.-%, more preferably 20 to 40 wt.-%, more preferably 23 to 38 wt.-%, more preferably 25 to 35 wt.-%, more preferably 27 to 33 wt.-%, and more preferably 29 to 31 wt.-% of aluminum, calculated as an element.
[0082] 5. The composite oxide according to any one of Examples 1 to 4, wherein in the composite oxide, the Co:Al weight ratio of cobalt to aluminum is in the range of 0.05:1 to 0.50:1, preferably 0.10:1 to 0.40:1, more preferably 0.12:1 to 0.30:1, more preferably 0.15:1 to 0.28:1, more preferably 0.18:1 to 0.25:1, and more preferably 0.20:1 to 0.22:1, more preferably in the range of 0.205:1 to 0.22:1, calculated as an element.
[0083] 6. The composite oxide according to any one of Examples 1 to 5, wherein the composite oxide contains LaAl 1-x Co x O3 phase, preferably LaAl 1-x Co x O3 perovskite phase, where 0 < x < 1, and where x is preferably in the range of 0.02 to 0.4, more preferably in the range of 0.03 to 0.3.
[0084] 7. The composite oxide according to Example 6, wherein the lattice parameter a of the LaAl 1-x Co x O3 phase is in the range of 3.7920 to preferably 3.7925 to more preferably 3.7928 to more preferably 3.7930 to and more preferably 3.7932 to the range of,
[0085] wherein in the composite oxide, the lattice parameter a of the LaAl 1-x Co x O3 phase is preferably determined according to the method of Reference Example 1.
[0086] 8. The composite oxide according to Example 6 or 7, wherein the composite oxide contains the LaAl 1-x Co xO3 phase, the amount of which ranges from 5 to 50 wt.-%, preferably 10 to 40 wt.-%, more preferably 13 to 35 wt.-%, more preferably 15 to 33 wt.-%, more preferably 18 to 30 wt.-%, more preferably 21 to 27 wt.-%, and more preferably 23 to 25 wt.-%, based on 100 wt.-% of the composite oxide
[0087] In the composite oxide, LaAl 1-x Co x The amount of the O3 phase is preferably determined according to the method of Reference Example 1.
[0088] 9. The composite oxide as described in any one of embodiments 1 to 8, wherein the composite oxide comprises LaCoAl 11 O 19 phase, preferably LaCoAl 11 O 19 Hexaaluminate phase.
[0089] 10. The composite oxide as described in Example 9, wherein the composite oxide comprises the LaCoAl 11 O 19 phase, the amount of which ranges from 40 to 90 wt.-%, preferably from 50 to 80 wt.-%, more preferably from 55 to 75 wt.-%, more preferably from 58 to 70 wt.-%, more preferably from 60 to 66 wt.-%, and more preferably from 62 to 64 wt.-%, based on 100 wt.-% of the composite oxide
[0090] In the composite oxide, LaCoAl 11 O 19 The amount of the phase is preferably determined according to the method of Reference Example 1.
[0091] 11. The composite oxide according to any one of embodiments 1 to 10, wherein the composite oxide comprises LaAl 1- x Co x O3 phase and LaCoAl 11 O 19 phase, in which the LaAl 1-x Co x O3 phase and LaCoAl 11 O 19 LaAl 1-x Co x O3:LaCoAl 11 O 19The weight ratio is in the range of 0.05:1 to 0.70:1, preferably 0.1:1 to 0.60:1, more preferably 0.15:1 to 0.55:1, more preferably 0.20:1 to 0.50:1, more preferably 0.25:1 to 0.48:1, more preferably 0.30:1 to 0.45:1, more preferably 0.35:1 to 0.42:1, and more preferably 0.37:1 to 0.39:1,
[0092] In the composite oxide, LaAl 1-x Co x O3 phase and the LaCoAl 11 O 19 The respective amounts of the phases are preferably determined according to the method of Reference Example 1.
[0093] 12. The composite oxide of any one of Embodiments 1 to 11, wherein the composite oxide comprises a La(OH) 3 phase.
[0094] 13. A composite oxide as described in Example 12, wherein the composite oxide contains the La(OH)3 phase in an amount ranging from 0.1 to 1.5 wt.-%, preferably 0.3 to 1.0 wt.-%, more preferably 0.5 to 0.8 wt.-%, and more preferably 0.6 to 0.7 wt.-%, based on 100 wt.-% of the composite oxide.
[0095] The amount of the La(OH)3 phase in the composite oxide is preferably determined according to the method of Reference Example 1.
[0096] 14. The composite oxide of any one of embodiments 1 to 13, wherein the composite oxide comprises a CoAl2O4 phase, preferably a CoAl2O4 spinel phase.
[0097] 15. The composite oxide of embodiment 14, wherein the composite oxide comprises the CoAl2O4 phase in an amount ranging from 1.0 to 10 wt.-%, preferably 1.5 to 7.0 wt.-%, more preferably 2.0 to 5.0 wt.-%, more preferably 2.5 to 4.0 wt.-%, more preferably 2.8 to 3.5 wt.-%, and more preferably 3.0 to 3.2 wt.-%, based on 100 wt.-% of the composite oxide.
[0098] The amount of the CoAl2O4 phase in the composite oxide is preferably determined according to the method of Reference Example 1.
[0099] 16. The composite oxide as described in any one of embodiments 1 to 15, wherein the composite oxide comprises LaAl 1- x Co x O3 phase and CoAl2O4 phase, in which the LaAl1-x Co x O3 phase and the CoAl2O4 phase 1-x Co x The O3:CoAl2O4 phase weight ratio is in the range of 1.0:1 to 15:1, preferably 2.0:1 to 12:1, more preferably 4.0:1 to 10:1, more preferably 6.0:1 to 9.0:1, more preferably 7.0:1 to 8.5:1, more preferably 7.5:1 to 8.2:1, and more preferably 7.8:1 to 7.9:1,
[0100] In the composite oxide, LaAl 1-x Co x The respective amounts of the O3 phase and the CoAl2O4 phase are preferably determined according to the method of Reference Example 1.
[0101] 17. The composite oxide as described in any one of embodiments 1 to 16, wherein the composite oxide comprises LaCoAl 11 O 19 phase and CoAl2O4 phase, in which the LaCoAl 11 O 19 The LaCoAl2O4 phase 11 O 19 :CoAl2O4 phase weight ratio is in the range of 1:1 to 50:1, preferably 3:1 to 45:1, more preferably 5:1 to 40:1, more preferably 9:1 to 35:1, more preferably 11:1 to 30:1, more preferably 13:1 to 28:1, more preferably 15:1 to 26:1, more preferably 18:1 to 24:1, and more preferably 20:1 to 22:1,
[0102] In the composite oxide, LaCoAl 11 O 19 The phase and the respective amounts of the CoAl2O4 phase are preferably determined according to the method of Reference Example 1.
[0103] 18. A composite oxide as described in any one of embodiments 1 to 17, wherein the composite oxide exhibits a crystallinity ranging from 80% to 100%, preferably 85% to 99%, more preferably 88% to 97%, more preferably 90% to 95%, and more preferably 91% to 93%,
[0104] The crystallinity of the composite oxide is preferably determined according to the method of Reference Example 1.
[0105] 19. The composite oxide of any one of embodiments 1 to 18, wherein 99 to 100 wt-%, preferably 99.5 to 100 wt-%, more preferably 99.9 to 100 wt-% of the composite oxide consists of oxygen, lanthanum, aluminum, cobalt and optionally hydrogen.
[0106] 20. The composite oxide according to any one of embodiments 1 to 19, wherein the composite oxide is in the form of a powder or a molded article, preferably in the form of a molded article.
[0107] 21. The composite oxide according to embodiment 20, wherein 99 to 100 wt-%, preferably 99.5 to 100 wt-%, more preferably 99.9 to 100 wt-% of the powder or the molded article consists of the composite oxide.
[0108] 22. The composite oxide of any one of embodiments 1 to 21, wherein the composite oxide is obtained or obtainable according to the method of any one of embodiments 23 to 39.
[0109] 23. A method for producing a composite oxide, preferably a composite oxide according to any one of embodiments 1 to 21, the method comprising
[0110] (i) preparing a mixture of one or more Al sources, one or more Co sources and one or more La sources;
[0111] (ii) adding an acidic aqueous solution to the mixture prepared in (i);
[0112] (iii) homogenizing the mixture obtained in (ii),
[0113] (iv) optionally shaping the mixture obtained in (iii), preferably by extrusion, to obtain a shaped body;
[0114] (v) optionally drying the mixture obtained in (iii) or the shaped body obtained in (iv);
[0115] (vi) optionally pre-calcining the mixture obtained in (iii) or (v), or the shaped body obtained in (iv) or (v);
[0116] (vii) optionally grinding the dried and / or precalcined mixture or shaped body obtained in (v) or (vi);
[0117] (viii) optionally tableting the ground product obtained in (vii);
[0118] (ix) calcining the mixture obtained in (iii), (v), or (vi), or the shaped body obtained in (iv), (v), or (vi), or the ground product obtained in (vii), or the tableted product obtained in (viii).
[0119] 24. A method as described in Example 23, wherein the one or more Al sources are selected from the group consisting of aluminum trihydroxide, Al2O3·0.5H2O, Al2O3, AlO(OH) - preferably boehmite, sodium aluminate and a mixture of two or more thereof, preferably selected from the group consisting of gibbsite (α-aluminum trihydroxide), bayerite (β-aluminum trihydroxide), nordstrandite (γ-aluminum trihydroxide), pseudo-amorphous aluminum trihydroxide, Al2O3·0.5H2O, Al2O3, AlO(OH) - preferably boehmite, sodium aluminate and a mixture of two or more thereof, wherein the one or more alumina sources are more preferably AlO(OH).
[0120] 25. A method as described in Example 23 or 24, wherein the one or more Co sources are selected from the group consisting of cobalt carbonate, cobalt oxalate, cobalt acetate, cobalt tartrate, cobalt formate, cobalt sulfate, cobalt sulfide, cobalt fluoride, cobalt chloride, cobalt bromide and cobalt iodide, wherein the one or more Co sources are preferably cobalt carbonate, more preferably cobalt carbonate, wherein the cobalt carbonate more preferably comprises, more preferably is CoCO3y·H2O, wherein 0≤y≤7, preferably 0≤y≤6.
[0121] 26. A method as described in any one of embodiments 23 to 25, wherein the one or more La sources are selected from the group consisting of lanthanum carbonate, lanthanum oxalate, lanthanum acetate, lanthanum tartrate, lanthanum formate, lanthanum sulfate, lanthanum sulfide, lanthanum fluoride, lanthanum chloride, lanthanum bromide and lanthanum iodide, wherein the one or more La sources are preferably lanthanum carbonate, wherein the lanthanum carbonate more preferably comprises, more preferably is, La2(CO3)3·xH2O, wherein 0≤x≤10, more preferably 0≤x≤6.
[0122] 27. The method of any one of embodiments 23 to 26, wherein the mixture in (i) is prepared by kneading the one or more Al, Co and La sources.
[0123] 28. A method as described in any one of Examples 23 to 27, wherein the acidic aqueous solution added in (ii) comprises one or more of formic acid, acetic acid, propionic acid, nitric acid, nitrous acid, citric acid, tartaric acid and oxalic acid, preferably one or more of formic acid and nitric acid, and wherein the acidic aqueous solution added in (ii) more preferably comprises formic acid.
[0124] 29. The process of any one of embodiments 23 to 28, wherein the homogenization in (iii) is achieved by stirring, preferably kneading, the mixture obtained in (ii).
[0125] 30. The method of any one of embodiments 23 to 29, wherein the drying in (v) is carried out at a temperature in the range of 80°C to 150°C, preferably in the range of 95°C to 120°C, more preferably in the range of 100°C to 110°C.
[0126] 31. The method of any one of embodiments 23 to 30, wherein the drying in (v) is performed for a duration in the range of 4 to 18 h, preferably in the range of 6 to 12 h, more preferably in the range of 8 to 10 h.
[0127] 32. The method of any one of embodiments 23 to 31, wherein the pre-calcination in (vi) is carried out at a temperature in the range of 300°C to 600°C, preferably in the range of 350°C to 500°C, more preferably in the range of 400°C to 450°C.
[0128] 33. The method of any one of embodiments 23 to 32, wherein the pre-calcination in (vi) is carried out for a duration in the range of 1 to 8 h, preferably in the range of 3 to 5 h, more preferably in the range of 3.5 to 4.5 h.
[0129] 34. The method of any one of embodiments 23 to 33, wherein the calcination in (ix) is carried out at a temperature in the range of 800°C to 1500°C, preferably in the range of 1000°C to 1400°C, more preferably in the range of 1100°C to 1300°C.
[0130] 35. The method of any one of embodiments 23 to 34, wherein the calcination in (ix) is carried out for a duration in the range of 1 to 8 h, preferably in the range of 3 to 5 h, more preferably in the range of 3.5 to 4.5 h.
[0131] 36. A composite oxide as obtainable or obtained according to the method of any one of embodiments 23 to 35.
[0132] 37. A method for producing a catalyst for converting hydrocarbons into synthesis gas, the method comprising
[0133] (1) providing a composite oxide according to any one of Examples 1 to 22 and 36, or preparing a composite oxide according to the method according to any one of Examples 23 to 35;
[0134] (2) Reducing the composite oxide prepared in (1) to obtain a catalyst.
[0135] 38. A method as described in Example 37, wherein the reduction in (2) is carried out in an atmosphere comprising one or more reducing agents, wherein the one or more reducing agents comprise one or more of methane, hydrogen and carbon monoxide, preferably methane and / or hydrogen, wherein methane is more preferably used as the reducing agent in (2).
[0136] 39. A method as described in Example 37 or 38, wherein the reduction in (2) is carried out at a temperature in the range of 500°C to 1,200°C, preferably 600°C to 1,100°C, more preferably 700°C to 1,050°C, more preferably 750°C to 1,000°C, more preferably 800°C to 950°C, and more preferably 850°C to 900°C.
[0137] 40. The method of any one of embodiments 37 to 39, wherein the reduction in (2) is carried out at a pressure in the range of 5 to 40 bar, preferably 10 to 35 bar, more preferably 12 to 30 bar, more preferably 14 to 25 bar, more preferably 16 to 22 bar, and more preferably 18 to 20 bar.
[0138] 41. The method of any one of embodiments 37 to 40, wherein the reduction in (2) is performed for a duration ranging from 0.5 to 24 h, preferably 1 to 18 h, more preferably 3 to 10 h, and more preferably 5 to 7 h.
[0139] 42. A catalyst for converting hydrocarbons into synthesis gas as obtainable or obtained according to the method of any one of embodiments 37 to 41.
[0140] 43. A method for converting hydrocarbons into synthesis gas, the method comprising
[0141] (A) providing the composite oxide according to any one of Embodiments 1 to 22 and 36, or the catalyst according to Embodiment 42;
[0142] (B) preparing a gas stream comprising one or more hydrocarbons and one or more of CO2 and H2O;
[0143] (C) contacting the gas stream prepared in (B) with the composite oxide provided in (A) at a temperature ranging from 700°C to 1,200°C, preferably 750°C to 1,100°C, more preferably 800°C to 1,050°C, more preferably 850°C to 1,000°C, and more preferably 900°C to 950°C.
[0144] 44. The method of embodiment 43, wherein the gas stream prepared in (B) comprises one or more hydrocarbons, CO2 and H2O.
[0145] 45. A method as described in Example 43 or 44, wherein the one or more hydrocarbons are selected from the group consisting of C1-C10 alkanes, preferably C1-C8 alkanes, more preferably C1-C6 alkanes, more preferably C1-C4 alkanes, more preferably C1-C3 alkanes, and more preferably C1-C2 alkanes, wherein the gas stream prepared in (B) more preferably comprises one or more of methane, ethane and propane, wherein the gas stream prepared in (B) more preferably comprises methane and / or ethane, preferably methane, wherein the one or more hydrocarbons contained in the gas stream prepared in (B) more preferably consist of methane and / or ethane, preferably methane.
[0146] 46. A method as described in any of Examples 43 to 45, wherein the gas stream prepared in (B) contains 20 to 80 vol.-%, preferably 25 to 60 vol.-%, more preferably 30 to 50 vol.-%, more preferably 35 to 45 vol.-%, and more preferably 38 to 42 vol.-% of the one or more hydrocarbons.
[0147] 47. A method as described in any one of Examples 43 to 46, wherein the gas stream prepared in (B) contains 20 to 80 vol.-%, preferably 25 to 60 vol.-%, more preferably 30 to 50 vol.-%, more preferably 35 to 45 vol.-%, and more preferably 38 to 42 vol.-% CO2.
[0148] 48. The method of any one of embodiments 43 to 47, wherein the gas stream prepared in (B) comprises 1 to 30 vol.-%, preferably 5 to 25 vol.-%, more preferably 10 to 20 vol.-%, more preferably 12 to 18 vol.-%, and more preferably 14 to 16 vol.-% H2O.
[0149] 49. A method as described in any one of Examples 43 to 48, wherein the gas stream prepared in (B) further comprises one or more inert gases, wherein these inert gases are preferably selected from the group consisting of rare gases, nitrogen and mixtures of two or more thereof, wherein more preferably the gas stream further comprises nitrogen and / or argon, preferably nitrogen.
[0150] 50. A method as described in Example 49, wherein the gas stream prepared in (B) contains 0 to 25 vol.-%, preferably 0.5 to 15 vol.-%, more preferably 1 to 10 vol.-%, more preferably 3 to 8 vol.-%, and more preferably 4 to 6 vol.% of the one or more inert gases.
[0151] 51. The method of any one of embodiments 43 to 50, wherein the contacting in (C) is carried out at a pressure in the range of 5 to 40 absolute bar, preferably 10 to 35 absolute bar, more preferably 12 to 30 absolute bar, more preferably 14 to 25 absolute bar, more preferably 16 to 22 absolute bar, and more preferably 18 to 20 absolute bar.
[0152] 52. The method of any one of embodiments 43 to 51, wherein the contacting in (C) is carried out at a temperature of 500 to 25,000 h. -1 , preferably 1,000 to 15,000h -1 , more preferably 3,000 to 10,000h -1 , more preferably 4,000 to 8,000h -1 , and more preferably 5,000 to 7,000h -1 The gas hourly space velocity is within the range. BRIEF DESCRIPTION OF THE DRAWINGS
[0153] Figure 1 Shown are the results of TPR analysis of samples from Comparative Example 1 and Examples 4 to 6, respectively, as performed according to Reference Example 2. In the figure, time in minutes is plotted along the abscissa.
[0154] Figure 2 Shown are the results of TPR analysis of samples from Comparative Example 1 and Examples 4 to 6, respectively, as performed according to Reference Example 2. In the figure, temperature in °C is plotted along the abscissa.
[0155] Figure 3 Shown are the results of TPR analysis of samples from Comparative Examples 2 and 8 and Examples 7 and 9, respectively, as performed according to Reference Example 2. In the figure, temperature in °C is plotted along the abscissa.
[0156] Figure 4 Shown are the results of the catalyst test according to Example 10 as carried out on samples from Comparative Examples 1 and 2 and Examples 3, 5 and 6. In the figure, the conversion of methane in % is plotted along the ordinate and the operating time of the catalyst in hours is plotted along the abscissa.
[0157] Figure 5 Shown are the results of the catalyst test according to Example 10 as carried out on samples from Comparative Examples 1 and 2 and Examples 3, 5 and 6. In the figure, the conversion of CO2 in % is plotted along the ordinate and the operating time of the catalyst in hours is plotted along the abscissa.
[0158] Experimental Section
[0159] The present invention is further illustrated by the following examples, comparative examples and reference examples.
[0160] Reference Example 1: Composition and structure analysis by X-ray diffraction
[0161] Powder X-ray diffraction (PXRD) data were collected using a laboratory diffractometer (D8 Discover, Bruker AXS GmbH, Karlsruhe). The instrument was equipped with a molybdenum X-ray tube (40mA, 40kV). Characteristic K-α radiation was monochromatized using a bent germanium Johansson type primary monochromator. Data were collected under Bragg-Brentano reflection geometry (2-40 ° (2θ), 0.02 ° step length, 2.4s / step). LYNXEYE XE area detector was used to collect scattered X-ray signals. Powder was ground using an IKA tube mill and a MT40.100 disposable grinding chamber. Powder was placed in a sample holder and flattened using a glass plate. Data analysis was performed using DIFFRAC.EVA V4 and DIFFRAC.TOPAS V4 software (Bruker AXS). DIFFRAC.EVA was used to evaluate crystallinity. The default values were used as input values for the algorithm (DIFFRAC.EVA User Manual, 2014, Bruker AXS, Karlsruhe). All other parameters were determined using DIFFRAC.TOPAS. 11 O 19 The entire diffraction pattern was simulated for the crystal structures of , rhombohedral LaAlO3, cubic CoAl2O4, hexagonal La(OH)3, cubic Co-doped LaAlO3 and corundum. During the simulation, 29 parameters were refined to fit the simulated diffraction to the measured data. These parameters are listed in Table 1 below.
[0162] Table 1: Parameters used for refinement
[0163]
[0164]
[0165] *Use the March-Dollase model along the (1 1 0) direction.
[0166] All crystal structures used were retrieved from the Inorganic Crystal Structure Database (ICSD) (ICSD, FIZ Karlsruhe (https: / / icsd.fiz-karlsruhe.de / )) or Pearson's Crystal Data (PCD) (Pearson's Crystal Data–Crystal Structure Database for Inorganic Compounds, 2016 / 2017 release, ASM International, Materials Park, Ohio, USA). The reference numbers of the structures used are listed in Table 2 below.
[0167] Table 2: Numbers of structures used
[0168] ICSD Number PCD Number <![CDATA[Hexagonal LaCoAl 11 O 19 > 1502158 <![CDATA[Cubic Co-doped LaAlO3]]> 1501066 <![CDATA[Rhombohedral LaAlO3]]> 28629 Corundum 1520618 <![CDATA[Cubic CoAl2O4]]> 163275 <![CDATA[Hexagonal La(OH)3]]> 192271 <![CDATA[Cubic LaAlO3]]> 170772
[0169] Crystallite size values are those reported as Lvol-FWHM in DIFFRAC.TOPAS. To ensure reliable crystallite size values, the diffractometer geometry was entered into the software to enable calculation of the instrument resolution based on the fundamental parameter method (DIFFRAC.TOPAS User Manual, 2014, Bruker AXS, Karlsruhe). Scaling factors were recalculated by DIFFRAC.TOPAS into mass percentage values and reported.
[0170] Reference Example 2: Temperature Programmed Reduction (TPR) Analysis
[0171] The reduction behavior of the molded article was determined by programmed temperature reduction. A sample of 190 mg of particles with an average particle size between 0.2 and 0.4 mm was used. As feed gas, a flow of 5 volume-% hydrogen in argon was used, wherein the feed rate was set to 50 ml / min. During the measurement, the temperature was increased from room temperature to 950° C. at a heating rate of 5 K / min. The thermal conductivity detector (TCD) signal relative to the temperature was recorded to obtain a TPR curve. The TPR curves of Examples 4-6 and Comparative Example 1 are shown in FIG. Figure 1 and 2 As shown, and those of Examples 7 and 9 and Comparative Examples 2 and 8 are as Figure 3 shown.
[0172] Comparative Example 1: Preparation of composite oxides of Co, La and Al
[0173] 70 kg of aqueous AlOOH (Disperal; Sasol; containing 77.6 wt-% Al, calculated as Al2O3), 13.04 kg of cobalt(II) carbonate hydrate (containing 55.92 wt-% Co, calculated as CoO; Umicore), 34.37 kg of lanthanum(III) carbonate hydrate (containing 49.26 wt-% La, calculated as La2O3; InnerMongolia) were premixed in a Koller or mixer for a few minutes. Then, 50.79 kg of aqueous formic acid (containing 37 wt-% formic acid; based on formic acid with 98-100 wt-%, Bernd Kraft GmbH, CAS#: 64-18-6) were added in three portions under mixing, wherein the first portion contained about 50 wt-%, the second and third portions each about 25 wt-% of the total aqueous formic acid, and a dough-like homogeneous pink mass was formed. Appropriate amounts of Disperal, CoCO3, La2(CO3)3 and 37wt% aqueous HCOOH were mixed in a kneader. The kneaded mass was then formed into 4mm ropes. The ropes were dried at 90°C for 10h and subsequently calcined at 400°C for 4h. The extrudates were subjected to a tabletting step to form quadrilateral tablets. Thereafter, the calcined extrudates were ground. The material was then sieved using a sieve with a mesh of 1000 microns. The sieved powder was then mixed with 3 wt% of graphite (Asbury Graphite 3160) and 3 wt% of microcrystalline cellulose (Vivapur SCG102). The resulting mixture was tableted into a molded article with a four-hole cross section. The molded article had a diameter of 16.74mm and a height of 9.84mm. The tablets were calcined.
[0174] For calcination, the molded article was heated to a temperature of 700° C. within 3 hours and the temperature was maintained for 1 hour. The molded article was then further heated to a temperature in the range of 1170° C. to 1200° C. and the temperature was maintained in this range for 4 hours. Calcination was performed in an annealing furnace.
[0175] Then, the molded article was split into particles having an inner diameter of 0.5 to 1 mm.
[0176] Comparative Example 2: Preparation of composite oxides of Co, La and Al
[0177] 30.7 kg of aqueous AlOOH (Disperal; Sasol; containing 77.9 wt.-% Al, calculated as Al2O3), 5.5 kg of cobalt(II) carbonate hydrate (containing 46 wt.-% Co; Umicore, Todini), 16.1 kg of lanthanum(III) carbonate hydrate (containing 39.3 wt.-% La; Mongolia Baotuo Steel Rare Earth Int. trade co. ltd) were premixed in a kneader for a few minutes. Then, 23 kg of aqueous formic acid (containing 37 wt.-% formic acid; based on formic acid with 98-100 wt.-%, BASF SE) was added under mixing and a dough-like homogeneous pink mass was formed.
[0178] The kneaded mass is then formed into 6 mm ropes. The ropes are dried at 95°C-120°C for 10 h and subsequently calcined at 400°C-440°C for 4 h. They are then split into particles with an inner diameter of 0.5-1 mm. The split particles are calcined before the catalytic test. For calcination, the molded article is heated to a temperature of 700°C within 3 hours and the temperature is maintained for 1 hour. The molded article is then further heated to a temperature of 1200°C and the temperature is maintained for 4 hours. Calcination is carried out in an annealing furnace.
[0179] Example 3: Preparation of composite oxides of Co, La and Al
[0180] 162.36 g of aqueous AlOOH (Disperal; Sasol; containing 71.6 wt.-% Al, calculated as Al2O3), 29.59 g of cobalt(II) carbonate hydrate (containing 46 wt.-% Co; abcr Germany GmbH), 97.57 g of lanthanum(III) carbonate hydrate (containing 41 wt.-% La; Alfa Aesar USA GmbH & CoKG) were premixed in a kneader for a few minutes. Then, 140 ml of aqueous formic acid (containing 37 wt.-% formic acid; based on formic acid with 98-100 wt.-%, Bernd Kraft GmbH) were added with mixing and a dough-like homogeneous pink mass was formed.
[0181] The kneaded mass was then formed into 3.5 mm ropes. The ropes were dried at 90° C. for 16 h, subsequently calcined at 400° C. for 4 h and then split into particles with an inner diameter of 0.5-1 mm. The split particles were calcined before the catalytic test. For calcination, the molded article was heated to a temperature of 700° C. within 3 hours and the temperature was maintained for 1 hour. The molded article was then further heated to a temperature of 1200° C. and the temperature was maintained for 4 hours. Calcination was carried out in an annealing furnace.
[0182] Example 4: Preparation of composite oxides of Co, La and Al
[0183] 165.8 g of aqueous AlOOH (Disperal; Sasol; containing 77.6 wt.-% Al, calculated as Al2O3), 30.9 g of cobalt(II) carbonate hydrate (containing 45 wt.-% Co; ABCR batch 1102550), 119.5 g of lanthanum(III) carbonate hydrate (containing 41 wt.-% La; Alfa Aesar batch Y04D030) were premixed in a kneader for a few minutes. Then, 120 ml of aqueous formic acid (containing 30 wt.-% formic acid; based on formic acid with 98-100 wt.-%, Bernd Kraft GmbH) were added with mixing and a dough-like homogeneous pink mass was formed.
[0184] The kneaded mass was then formed into 3.5 mm ropes. The ropes were dried at 90° C. for 16 h, subsequently calcined at 400° C. for 4 h and then split into particles with an inner diameter of 0.5-1 mm. The split particles were calcined before the catalytic test. For calcination, the molded article was heated to a temperature of 700° C. within 3 hours and the temperature was maintained for 1 hour. The molded article was then further heated to a temperature of 1200° C. and the temperature was maintained for 4 hours. Calcination was carried out in an annealing furnace.
[0185] Example 5: Preparation of composite oxides of Co, La and Al
[0186] 155.8 g of aqueous AlOOH (Disperal; Sasol; containing 77.9 wt.-% Al, calculated as Al2O3), 29.7 g of cobalt(II) carbonate hydrate (containing 46 wt.-% Co; ABCR batch 1102550), 132.1 g of lanthanum(III) carbonate hydrate (containing 41 wt.-% La; Alfa Aesar batch Y04D030) were premixed in a kneader for a few minutes. Then, 140 ml of aqueous formic acid (containing 37 wt.-% formic acid; based on formic acid with 98-100 wt.-%, Bernd Kraft GmbH) were added with mixing and a dough-like homogeneous pink mass was formed.
[0187] The kneaded mass was then formed into 3.5 mm ropes. The ropes were dried at 90° C. for 16 h, subsequently calcined at 400° C. for 4 h and then split into particles with an inner diameter of 0.5-1 mm. The split particles were calcined before the catalytic test. For calcination, the molded article was heated to a temperature of 700° C. within 3 hours and the temperature was maintained for 1 hour. The molded article was then further heated to a temperature of 1200° C. and the temperature was maintained for 4 hours. Calcination was carried out in an annealing furnace.
[0188] Example 6: Preparation of composite oxides of Co, La and Al
[0189] 151.9 g of aqueous AlOOH (Disperal; Sasol; containing 77.9 wt.-% Al, calculated as Al2O3), 29.7 g of cobalt(II) carbonate hydrate (containing 46 wt.-% Co; ABCR batch 1102550), 152.5 g of lanthanum(III) carbonate hydrate (containing 41 wt.-% La; Alfa Aesar batch Y04D030) were premixed in a kneader for a few minutes. Then, 140 ml of aqueous formic acid (containing 51 wt.-% formic acid; based on formic acid with 98-100 wt.-%, Bernd Kraft GmbH) were added with mixing and a dough-like homogeneous pink mass was formed.
[0190] The kneaded mass was then formed into 3.5 mm ropes. The ropes were dried at 90° C. for 16 h, subsequently calcined at 400° C. for 4 h and then split into particles with an inner diameter of 0.5-1 mm. The split particles were calcined before the catalytic test. For calcination, the molded article was heated to a temperature of 700° C. within 3 hours and the temperature was maintained for 1 hour. The molded article was then further heated to a temperature of 1200° C. and the temperature was maintained for 4 hours. Calcination was carried out in an annealing furnace.
[0191] Example 7: Preparation of composite oxides of Co, La and Al
[0192] 160 g of aqueous AlOOH (Disperal; Sasol; containing 77.6 wt.-% Al, calculated as Al2O3), 31.1 g of cobalt(II) carbonate hydrate (containing 46 wt.-% Co; Umicore batch 29371A0205 / BASF AG), 160.1 g of lanthanum(III) carbonate hydrate (containing 41 wt.-% La; Inner Mongolia Baotou Steel Rare Earth International Trading Co., Ltd.) were premixed in a kneader for a few minutes. Then, 140 ml of aqueous formic acid (containing 51 wt.-% formic acid; based on formic acid with 98-100 wt.-%, Bernd Kraft GmbH) were added with mixing and a dough-like homogeneous pink mass was formed.
[0193] The kneaded mass was then formed into 3.5 mm ropes. The ropes were dried at 90° C. for 16 h, subsequently calcined at 400° C. for 4 h and then split into particles with an inner diameter of 0.5-1 mm. The split particles were calcined before the catalytic test. For calcination, the molded article was heated to a temperature of 700° C. within 3 hours and the temperature was maintained for 1 hour. The molded article was then further heated to a temperature of 1200° C. and the temperature was maintained for 4 hours. Calcination was carried out in an annealing furnace.
[0194] Comparative Example 8: Preparation of composite oxides of Co, La and Al
[0195] 160 g of aqueous AlOOH (Disperal; Sasol; containing 77.6 wt.-% Al, calculated as Al2O3), 28.6 g of cobalt(II) carbonate hydrate (containing 46 wt.-% Co; Umicore batch 29371A0205 / BASF AG), 80.5 g of lanthanum(III) carbonate hydrate (containing 41 wt.-% La; Inner Mongolia Baotou Steel Rare Earth International Trading Co., Ltd.) were premixed in a kneader for a few minutes. Then, 120 ml of aqueous formic acid (containing 37 wt.-% formic acid; based on formic acid with 98-100 wt.-%, Bernd Kraft GmbH) were added with mixing and a dough-like homogeneous pink mass was formed.
[0196] The kneaded mass was then formed into 3.5 mm ropes. The ropes were dried at 90° C. for 16 h, subsequently calcined at 400° C. for 2 h and then split into particles with an inner diameter of 0.5-1 mm. The split particles were calcined before the catalytic test. For calcination, the molded article was heated to a temperature of 700° C. within 3 hours and the temperature was maintained for 1 hour. The molded article was then further heated to a temperature of 1200° C. and the temperature was maintained for 4 hours. Calcination was carried out in an annealing furnace.
[0197] Example 9: Preparation of composite oxides of Co, La and Al
[0198] 160 g of aqueous AlOOH (Disperal; Sasol; containing 77.6 wt.-% Al, calculated as Al2O3), 31.9 g of cobalt(II) carbonate hydrate (containing 46 wt.-% Co; Umicore batch 29371A0205), 186.3 g of lanthanum(III) carbonate hydrate (containing 41 wt.-% La; Inner Mongolia Baotou Steel Rare Earth International Trading Co., Ltd.) were premixed in a kneader for a few minutes. Then, 140 ml of aqueous formic acid (containing 59 wt.-% formic acid; based on formic acid with 98-100 wt.-%, Bernd Kraft GmbH) were added with mixing and a dough-like homogeneous pink mass was formed.
[0199] The kneaded mass was then formed into 3.5 mm ropes. The ropes were dried at 90° C. for 16 h, subsequently calcined at 400° C. for 2 h and then split into particles with an inner diameter of 0.5-1 mm. The split particles were calcined before the catalytic test. For calcination, the molded article was heated to a temperature of 700° C. within 3 hours and the temperature was maintained for 1 hour. The molded article was then further heated to a temperature of 1200° C. and the temperature was maintained for 4 hours. Calcination was carried out in an annealing furnace.
[0200] Catalyst characterization
[0201] As can be seen in the elemental analysis shown in Table 1, the La content is increased while both Al and Co are decreased in the inventive examples, resulting in samples having an increased amount of LaAlO 3 (Co-doped) phase (see Table 2).
[0202] Table 1. Elemental analysis of samples from the Examples (after the second calcination step).
[0203]
[0204]
[0205] Table 2. XRD analysis of samples from the examples (composition according to XRD phases in absolute numbers (wt.-%) and including any amorphous phases).
[0206]
[0207] from Figure 1 and 2 The results of the TPR analysis performed on Comparative Example 1 and Examples 4, 5 and 6 shown in FIG. 1 and FIG. 2 show that by increasing the amount of LaAlO3 (Co-doped) phase, a lower temperature peak appears in the TPR, which has a positive effect on the activation behavior. These observations are further analyzed by performing the TPR analysis on Comparative Examples 2 and 8 and Examples 7 and 9. Figure 3 The results of the TPR analysis shown in demonstrate that the latter examples have an increased amount of Co-doped LaAlO 3 and show a lower temperature peak in the TPR compared to the results obtained using the samples from Comparative Examples 2 and 8.
[0208] As can be seen from the results shown in Table 3, LaAl (Co) The lattice parameter a of the O3-phase decreases with decreasing Co content and increasing La content in the composite. This seems to be related to the fact that due to the 3+ Compared to Co 3+ The ionic radius of LaAl is slightly larger. (Co)When the O3-phase contains less cobalt, it will show a lower lattice parameter a value. (Co) O3- compared with the comparative example LaAl (Co) The O3-phase contains less cobalt.
[0209] Table 3. XRD analysis of samples from the Examples.
[0210]
[0211]
[0212] Example 10: Catalyst testing in methane reforming in the presence of H2O and CO2
[0213] Catalytic tests were performed on samples from comparative examples 1 and 2 and examples 3, 5 and 6 on a single reactor test unit. As gas feed, CO2, CH4, N2 and Ar were provided and controlled online by MFC. Water was added to the feed stream by an evaporator connected to a water reservoir. Analysis of the product gas composition was performed by online-GC using Ar as an internal standard. GC-analysis enabled H2, CO, CO2, CH4 and C2-components to be quantified. The duration of the GC-method was set to 24 min.
[0214] For catalytic testing, typically 15 ml of catalyst in cracked form (0.5-1.0 mm) was tested. The sample was placed in the isothermal zone of the reactor using ceramic fittings. Before starting the experiment, the back pressure was determined. All catalysts were tested at a pressure of 20 bar, with a pressure of 20 bar for the start-up phase (Phase #1) at 8000 h. -1 A feed of 95% N2 and 5% Ar was passed over the catalyst at a GHSV of 1.07 K / min, wherein the reactor was heated to 900°C (14 h) at a ramp rate of 1.07 K / min, followed by a feed of 80% N2, 5% Ar and 15% H2O, which was heated at 900°C for 8000 h. -1 After the start-up phase, each catalyst sample was tested under the conditions shown in Table 4 according to a test protocol consisting of 5 further phases.
[0215] Table 1. Test plan.
[0216]
[0217] As from Figure 4 and 5 The results of the catalyst tests shown in FIG. 4 show that methane ( Figure 4 ) and CO2( Figure 5), stage 3 is the activation stage, in which the conversion rate increases at a certain rate with the change of running time. In stages 4 and 5, the performance of the catalyst is usually fully exerted, and the conversion rate value may decrease due to the gradual deactivation of the catalyst, or remain constant as the reaction time increases.
[0218] Based on the quantification of the product gas flow, the CH4 conversion [1], CO2 conversion [2], H2 / CO ratio as well as the product gas composition and C2 component fraction were calculated.
[0219] CH4-conversion rate: X(CH4)=1-(CH4-out / CH4-in) [1]
[0220] CO2 conversion rate: X(CO2) = 1-(CO2-out / CO2-in) [2]
[0221] Furthermore, the relative conversions of CH4[3] and CO2[4] are calculated and presented in relation to the thermodynamic maximum conversion X_max (equilibrium composition). The equilibrium composition has been calculated accordingly taking into account the test conditions.
[0222] CH4-Relative conversion rate: X_relative(CH4)=X(CH4) / X_max(CH4)[3]
[0223] CO2-relative conversion rate: X_relative(CO2) = X(CO2) / X_max(CO2)[4]
[0224] As noted above, in Figure 4 and 5 The experimental conversions of the catalyst examples are compared in . As can be seen from the results, Example 3 already shows a significantly improved methane conversion during the activation phase compared to Comparative Examples 1 and 2 (see Figure 4 ), and the complete conversion of the sample from Example 3 in terms of methane and CO2 conversion is not only achieved long before the complete conversion of the samples from Comparative Examples 1 and 2, but is also significantly higher than the complete conversion rates of the latter (see respectively Figure 4 and 5 On the other hand, Examples 5 and 6 reveal a much easier activation which already clearly starts at 900° C., in particular for the sample from Example 6 (see Figure 4 and 5 stage (3)).
[0225] Thus, it has been found quite unexpectedly that the unique composition of the inventive samples results in a significant surge in conversion activity during the activation stage and provides significantly higher complete conversion at an earlier stage of the reaction than the samples from Comparative Examples 1 and 2.
[0226] citational references
[0227] -WO 2013 / 118078 A1
[0228] -WO 2014 / 135642 A1
[0229] -WO 2015 / 091310 A1
[0230] -US2016 / 0207031 A1
[0231] -US 9566571 B2
[0232] -WO 2014 / 001423 A1
[0233] -WO 2015 / 135968 A1
[0234] -WO 2016 / 062853 A1
[0235] - WO 2020 / 157202 A1.
Claims
1. A composite oxide comprising oxygen, lanthanum, aluminum and cobalt, wherein the weight ratio of cobalt to lanthanum (Co:La) in the composite oxide is in the range of 0.06:1 to 0.34:1, calculated as the element.
2. The composite oxide according to claim 1, wherein The composite oxide contains 1 to 15 wt.-% cobalt, calculated as the element.
3. The composite oxide according to claim 1 or 2, wherein The composite oxide contains 5 to 50 wt.-% lanthanum, calculated as the element.
4. The composite oxide according to any one of claims 1 to 3, wherein The composite oxide contains 5 to 60 wt.-% aluminum, calculated as the element.
5. The composite oxide according to any one of claims 1 to 4, wherein The Co:Al weight ratio of cobalt to aluminum in the composite oxide is in the range of 0.05:1 to 0.50:1, calculated as the element.
6. The composite oxide according to any one of claims 1 to 5, wherein The composite oxide contains LaAl 1-x Co x O3 phase, where 0 <x<1。 7. The composite oxide according to claim 6, wherein The LaAl 1-x Co x The lattice parameter a of the O3 phase is between 3.7920 and within the range.
8. The composite oxide according to any one of claims 1 to 7, wherein The composite oxide comprises LaCoAl 11 O 19 Mutually.
9. The composite oxide according to any one of claims 1 to 8, wherein The composite oxide exhibits a crystallinity ranging from 80% to 100%.
10. A method for producing a composite oxide according to any one of claims 1 to 9, the method comprising (i) preparing a mixture of one or more Al sources, one or more Co sources and one or more La sources; (ii) adding an acidic aqueous solution to the mixture prepared in (i); (iii) homogenizing the mixture obtained in (ii), (iv) optionally shaping the mixture obtained in (iii) to obtain a shaped body; (v) optionally drying the mixture obtained in (iii) or the shaped body obtained in (iv); (vi) optionally pre-calcining the mixture obtained in (iii) or (v), or the shaped body obtained in (iv) or (v); (vii) optionally grinding the dried and / or precalcined mixture or shaped body obtained in (v) or (vi); (viii) optionally tableting the ground product obtained in (vii); (ix) calcining the mixture obtained in (iii), (v), or (vi), or the shaped body obtained in (iv), (v), or (vi), or the ground product obtained in (vii), or the tableted product obtained in (viii).
11. A composite oxide obtainable or obtained according to the method of claim 10.
12. A method for producing a catalyst for converting hydrocarbons into synthesis gas, the method comprising (1) providing a composite oxide according to any one of claims 1 to 9 and 11, or preparing a composite oxide according to claim 10; (2) Reducing the composite oxide prepared in (1) to obtain a catalyst.
13. The method of claim 12, wherein: The reduction in (2) is performed in an atmosphere containing one or more reducing agents, wherein the one or more reducing agents contain one or more of methane, hydrogen and carbon monoxide.
14. A catalyst for converting hydrocarbons into synthesis gas, obtainable or obtained according to the process of claim 12 or 13.
15. A method for converting hydrocarbons into synthesis gas, the method comprising (A) providing the composite oxide according to any one of claims 1 to 9 and 11, or the catalyst according to claim 14; (B) preparing a gas stream comprising one or more hydrocarbons and one or more of CO2 and H2O; (C) contacting the gas stream prepared in (B) with the composite oxide provided in (A) at a temperature ranging from 700°C to 1,200°C.
Citation Information
Patent Citations
Process for producing a reforming catalyst and the reforming of methane
US20160207031A1
Hexaaluminate-comprising catalyst for the reforming of hydrocarbons and a reforming process
US9566571B2
Hexaaluminate-comprising catalyst for reforming of hydrocarbons and reforming process
WO2013118078A1
High-pressure process for carbon dioxide reforming of hydrocarbons in the presence of iridium-containing active masses
WO2014001423A1
Nickel hexaaluminate-containing catalyst for reforming hydrocarbons in the presence of carbon dioxide
WO2014135642A1